Honokiol in glioblastoma recurrence: a case report - Wang, Ce; Cai, Zehao; Huang, Yue; Liu, Xinrui; Liu, Xing; Chen, Feng; Li, Wenbin (Frontiers in Neurology, 2023)
Glioblastoma is the most common and aggressive primary tumor in the central nervous system. There is no standard of care for patients with recurrent GBM. Honokiol is a pleiotropic lignan and has the potential to be a potent and safe anticancer agent in human GBM when it is encapsulated by liposomes. We report an efficient and safe response to three phases of treatment with liposomal honokiol in a patient with recurrent glioblastoma.